Evolution of Retinitis to Macular Hole and Closure: OCT Insights into an Unusual Course of Ocular Toxoplasmosis - Subash Bhatta; Nayana Pant; Nola Pikacha (Case Reports in Ophthalmology)
Introduction: The aim of this study was to describe the distinctive optical coherence tomography (OCT) characteristics and the underlying mechanisms, leading to the uncommon occurrence of macular hole (MH) development in ocular toxoplasmosis. Case Presentation: A 13-year-old girl with a history of bilateral ocular toxoplasmosis presented with newly onset floaters and a progressive loss of vision in her right eye. Examination revealed macular chorioretinal scars in both eyes. Foveal area in the right eye also revealed some barely distinct creamy white lesions which were visible in OCT as punctate inner and outer retinitis with some full thickness lesions, indicating active disease in the right eye. Treatment with oral co-trimoxazole and prednisolone was initiated. At 2-week follow-up, there was complete necrosis of fovea, leading to formation of MH with an overhanging membrane. Rapid evolution continued with signs of progressive closure of the hole starting within a week of MH formation. At 4 months, the foveal contour had restored with some evidence of regeneration of external limiting membrane. However, a small outer layer defect persisted and visual acuity remained at 3/60, with only a minimal subjective improvement in visual function. Conclusion: Liquefactive necrosis of retina can lead to a rapid course of MH formation without the presence of visibly florid retinal lesions and vitritis in toxoplasmosis. Spontaneous closure of the MH is possible with medical treatment, but the visual prognosis remains uncertain, as the MH is mostly closed with disorganized retinal tissue. OCT is crucial for diagnosis and monitoring, underscoring the importance of immediate attention to new symptoms.